2012
DOI: 10.1097/brs.0b013e318241ad33
|View full text |Cite
|
Sign up to set email alerts
|

Ossification of the Posterior Longitudinal Ligament of the Cervical Spine

Abstract: OPLL should be managed on the basis of the consideration of its natural history. Elucidation of pathogenetic genes of OPLL will introduce a new approach for management of OPLL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
185
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(204 citation statements)
references
References 19 publications
1
185
0
1
Order By: Relevance
“…Ossification of the posterior longitudinal ligament (OPLL) is a pathological condition causing ectopic bone formation in the spine ligament [3,7,14]. It is known that the presence of OPLL does not always indicate cervical myelopathy, and clinical symptoms may occur only when the ossified ligament develops to a certain degree [17].…”
Section: Introductionmentioning
confidence: 99%
“…Ossification of the posterior longitudinal ligament (OPLL) is a pathological condition causing ectopic bone formation in the spine ligament [3,7,14]. It is known that the presence of OPLL does not always indicate cervical myelopathy, and clinical symptoms may occur only when the ossified ligament develops to a certain degree [17].…”
Section: Introductionmentioning
confidence: 99%
“…33 Recent research, however, has shown that OPLL has an incidence of 0.1%-1.7% among North Americans and Europeans with cervical spine disorders. 13,37 The increasing awareness of OPLL requires surgeons to be familiar with all viable treatment options.…”
mentioning
confidence: 99%
“…Matsunaga et al [2] found 71 % patients of OPLL without original myelopathy lived myelopathy-free during a 30-years follow-up, and advocated that preventive surgery was not necessary for non-myelopathic patients. We observed some cases of OPLL without symptoms of myelopathy (or not diagnosed myelopathy) who were rendered quadriplegic and/or presented with dyspnea after minor trauma like slipping from a chair in sitting position or cycling on macadam.…”
mentioning
confidence: 99%